Determinants of Carbon Disclosure: Board Size and Financial Performance - Rona Tumiur Mauli Carolin Simorangkir; Nurul Hidayah (Penerbit Goodwood, 2026)
Purpose: This study examines the influence of board characteristics (board size and gender diversity) and financial factors (profitability and leverage) on carbon-emission-disclosure practices among mining companies in an emerging market context. Methodology: Employing a quantitative approach with a causal research design, this study analyzes secondary data from 50 firm-year observations of mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Multiple linear regression analysis was performed using SPSS version 26. Results: The findings reveal that board size has a significant positive influence on carbon emission disclosure (? = 0.318, p < 0.05), supporting agency theory. However, board gender diversity, profitability, and leverage have no significant influence on carbon disclosure practices. Conclusions: This study concludes that larger boards are more effective in promoting carbon emission disclosure practices in Indonesian mining companies. The model explains 28.9% of the variance in the carbon emission disclosure. Limitations: This study focuses exclusively on Indonesian mining companies over a five-year period, which may limit its generalizability. Contributions: This study contributes to the environmental disclosure literature by providing empirical evidence from an emerging market context where carbon disclosure remains voluntary.